디자인 대학교육 연구에 나타난 연구주제 동향 분석 - 2012년~2018년 국내 학술지를 중심으로 - 방경란; Kyung-rhan Bang (한국디자인포럼, 2018)
연구배경 현재 대학의 디자인교육은 20세기 초부터 적용되었던 전통적인 조형표현 중심의 교육으로부터 사회변화의 새로운 패러다임에 따라 많은 변화가 진행되고 있다. 특히, 미래인재양성을 위해 대학에서의 디자인전공 통합 및 타 전공과의 융합교육이 빈번하게 이루어지면서 향후 한국 대학현실에 적합한 디자인교육의 방향설정이 시급한 상황이다. 연구방법 최근 디자인교육의 연구주제를 고찰하고 그 내용을 분석하여 디자인교육의 목표 및 내용의 변화에 대한 연구동향에 대하여 고찰하였다. 연구의 대상으로는 총 151편의 국내학술지를 중심으로 문헌조사방법으로 진행되었으며, 3가지의 키워드인 ‘기초’, ‘창의’, ‘융합’을 중심으로 디자인교육 전문가들의 3차 분석과정을 거쳐 각 주제별 10편씩 총 30편을 연구대상으로 선정하였다. 연구결과 분석결과‘기초 교육’연구에서는 조형표현중심의 교육사례, ‘창의교육’에서는 디자인 기반의 창의력 향상, ‘융합교육’은 디자인과 공학중심의 통합적 교육방향에 관한 것이 주요 내용이었다. 결론 최근 국내 대학에서의 디자인교육에 관한 연구는 기초교육의 조형표현중심으로부터 점차 창의성 향상에 대한 관심으로의 변화를 거치면서 타 학문과의 통합교육에 관한 내용 중심으로 변화되었다. 또한, 디자인 학문 단일의 세부전공에서의 교육연구에서 벗어나 인문과 공학과의 연계된 교육으로의 변화를 모색하고 있음을 알 수 있었다. Background At present, the design education of universities is undergoing a lot of changes according to the new paradigm of social change from education focusing on the traditional formative expression which was applied from the early 20th century. Especially, as the integrated design education and convergence education with other majors are carried out frequently in order to cultivate future talents, it is urgent to set direction of design education appropriate to the future reality of universities in Korea. Methods According to this background and necessity, this study examined the latest research topic of design education, analyzed its contents, and looked into research trends on the goal and changes in contents of design education. This study was carried out by the literature review method, focusing on total 151 academic journals in Korea. Based on these derived three core keywords-basic, creativity, convergence, the research subjects were selected through a third analysis on total 30 articles (10 articles for each core keyword) made by experts in design education. Result The result of this study shows that the main topic is ‘curriculum’ focusing on formative expression in ‘basic design’, ‘improvement’ of creativity based on design in ‘creativity’, and ‘integrated educational direction’ focusing on design and engineering in ‘convergence’. Conclusion In addition, research on the latest design education in domestic universities is gradually undergoing changes from basic design focusing on formative expression to the interest in improving creativity and to the integrated education with other disciplines. It is also found out that researches are seeking to changes into education linked to humanities and engineering beyond education and studies in the detailed major of a single design discipline.